The Youth Attitudes about Vaccines (YAV-5) scale: adapting the parent attitudes about childhood vaccines short scale for use with youth in German, French, and Italian in Switzerland, exploratory factor analysis and mokken scaling analysis. Issue 12 (2nd December 2021) - Olarewaju, Victoria O.; Jafflin, Kristen; Deml, Michael J.; Gültekin, Nejla; Muggli, Franco; Schärli, Susanna; Gruillot, Catherine; Kloetzer, Andrea; Huber, Benedikt M.; Merten, Sonja; Tarr, Philip E.
ABSTRACT: No validated measures of vaccine hesitancy (VH) for youth vaccination currently exist. We adapted the Parent Attitudes about Childhood Vaccines survey (PACV-15) for use in youth to create the version Youth Attitudes about Vaccines survey (YAV-14 and YAV-5), then translated it into three languages (German, French, and Italian). We administered the YAV-14 to 1, 003 youth aged 15–26 years in Switzerland. We used exploratory factor analysis and Mokken scale analysis to explore the psychometric properties, Cronbach's alpha to investigate the reliability for the YAV-14 and the YAV-5, but we only report results of the YAV-5 analysis here. We determined construct validity by logistic regression of the association between youth VH as measured by the YAV-5 and non-receipt of the first human papillomavirus (HPV) vaccine dose. EFA produced a single scale in German and French while two factors were obtained in Italian. All language versions fit the Mokken scale models with medium-scale strength. There was a significant association between VH and HPV vaccine non-receipt for the full sample (odds ratio (OR); 1.93, 95% confidence interval (CI); 1.31–2.85). Language-stratified analyses found a significant association between VH and non-immunization in the German-language sample. Our results demonstrate that the German version of YAV-5 is a valid and reliable scale for identifying vaccine hesitant youth regardless of sex, and the French version is a valid and reliable scale for identifying vaccine hesitant female youth. Further validation is needed for Italian and French-speaking male youth.